2021
DOI: 10.14712/23363177.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Vliv akademického optimismu na výsledky žáků středních škol

Abstract: Řada výzkumů ukázala vliv postojů učitelů na výsledky žáků. Jedním z konceptů, prostřednictvím kterého mohou být postoje učitelů operacionalizovány, je akademický optimismus. Zahrnuje vnímání vlastní účinnosti, důvěru v žáky a jejich rodiče a důraz na vzdělávací výsledky žáků. Vliv akademického optimismu na vzdělávací výsledky žáků byl u nás prokázán na nižším sekundárním stupni vzdělávání. Tato studie zkoumá jeho uplatnění na úrovni vyššího sekundárního stupně. Výzkum odpovídá na otázku, zda akademický optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Furthermore, this research showed that "children from families with lower socio-economic status, including lower levels of parental education, have lower aspirations for higher education" (p. 69). Straková, Simonová, and Soukup (2020), following previous studies and research, developed the construct of "academic optimism", which includes a teacher's perception of self-efficacy, trust in students and their parents, and an emphasis on students' educational outcomes. They found that academic optimism does not directly affect students' knowledge and skills in mathematics and reading literacy but affects other aspects, such as the sense of belonging to the school.…”
Section: Parents' Education and Children's Education Assumptions And ...mentioning
confidence: 99%
“…Furthermore, this research showed that "children from families with lower socio-economic status, including lower levels of parental education, have lower aspirations for higher education" (p. 69). Straková, Simonová, and Soukup (2020), following previous studies and research, developed the construct of "academic optimism", which includes a teacher's perception of self-efficacy, trust in students and their parents, and an emphasis on students' educational outcomes. They found that academic optimism does not directly affect students' knowledge and skills in mathematics and reading literacy but affects other aspects, such as the sense of belonging to the school.…”
Section: Parents' Education and Children's Education Assumptions And ...mentioning
confidence: 99%
“…V ČR proběhla pouze dvě šetření, která mapovala rozdíly mezi všemi středoškolskými programy ve znalostech jejich studentů v závěrečných fázích jejich studia. Jednalo se o Třetí mezinárodní výzkum matematického a přírodovědného vzdělávání (TIMSS) v roce 1995, který ukázal v mezinárodním srovnání jedny z největších rozdílů mezi žáky jednotlivých programů v matematické a přírodovědné gramotnosti (Straková et al, 1998)…”
Section: Poznatky O Rozdílech Mezi Středoškolskými Programyunclassified